Effect of Pregnancy Classes Plus Early Warning System on Postpartum Hemorrhage Prevention and Self-Efficacy - Sulistiawati Sulistiawati; Runjati Runjati; Hermien Nugraheni (Journal of Maternal and Child Health, 2026)
Background: Postpartum hemorrhage, defined as blood loss exceeding 500 ml after delivery, is a leading cause of maternal mortality in Indonesia. This condition can lead to serious consequences, including anemia, shock, and even death if not treated promptly and appropriately. Prevention efforts include educating pregnant women about early detection and preventive measures. One intervention is the implementation of pregnancy classes plus an Early Warning System (EWS) as a learning tool to improve mothers' self-efficacy and actions in preventing postpartum hemorrhage. The purpose of this study was to analyze the effect of pregnancy classes plus an early warning system on actions and self-efficacy in preventing postpartum hemorrhage. Subjects and Methods: This study used a True Experiment with a Pretest-Posttest with Control Group Design. The study location was the Gayamsari Community Health Center in Semarang City. Data collection was conducted from June to July 2025. The intervention group consisted of two groups: the intervention group, which received the pregnancy class with an Early Warning System (EWS), and the control group, which received a standard pregnancy class. The dependent variables studied were women's postpartum hemorrhage prevention practices and self-efficacy, while the independent variable was the early warning system (EWS) class. The analysis technique used was the Wilcoxon test. Results: Women in the intervention group reported higher postpartum hemorrhage prevention practices after the EWS class (median = 20; min-max = 13-20) compared to before the intervention (median = 10; min-max = 3-14) and was statistically significant (p <0.001). Women in the intervention group reported higher postpartum hemorrhage prevention practices after the EWS class (median = 52; min-max = 40-60) compared to before the intervention (median = 25; min-max = 20-35) and was statistically significant (p <0.001). Conclusion: The EWS class and early warning system have been shown to be effective in increasing postpartum hemorrhage prevention practices and efficacy, making them a safe and practical alternative for promotive and preventive interventions.